Omission of Adjuvant Chemotherapy Is Associated With Increased Mortality in Patients With T3N0 Colon Cancer With Inadequate Lymph Node Harvest. Issue 1 (January 2017) - Wells, Katerina O.; Hawkins, Alexander T.; Krishnamurthy, Devi M.; Dharmarajan, Sekhar; Glasgow, Sean C.; Hunt, Steven R.; Mutch, Matthew G.; Wise, Paul; Silviera, Matthew L.
Abstract : BACKGROUND: Adjuvant chemotherapy for T3N0 colon cancer is controversial. National guidelines recommend its use in patients with stage II with high-risk features, including lymph node harvest of less than 12, yet this treatment is underused. OBJECTIVE: The purpose of this study was to demonstrate that the use of adjuvant chemotherapy in patients with T3N0 adenocarcinoma with inadequate lymph node harvest is beneficial. DESIGN: This was a retrospective population-based study of patients with resected T3N0 adenocarcinoma of the colon. SETTINGS: The National Cancer Database was queried from 2003 to 2012. PATIENTS: A total of 134, 567 patients with T3N0 colon cancer were included in this analysis. MAIN OUTCOME MEASURES: The use of chemotherapy, short-term outcomes, and overall survival was evaluated. Clinicopathologic factors associated with omission of chemotherapy were also analyzed. RESULTS: Inadequate lymph node harvest was observed in 23.3% of patients, and this rate decreased over the study period from 46.8% in 2003 to 12.5% in 2012 ( p < 0.0001). Overall 5-year survival for patients with T3N0 cancer was 66.8%. Inadequate lymph node harvest among these patients was associated with lower overall 5-year survival (58.7% vs 69.8%; p < 0.001). The use of adjuvant chemotherapy among patients with T3N0 cancer after inadequate lymph node harvest was only 16.7%. In a multivariable analysis, factors associated with failure to receive chemotherapy included advanced age (OR = 0.44 (95% CI, 0.43–0.45)), increased comorbidities (OR = 0.7 (95% CI, 0.66–0.76)), and postoperative readmission (OR = 0.78 (95% CI, 0.67–0.91)). Patients with inadequate lymph node harvest who received adjuvant chemotherapy had improved 5-year survival (chemotherapy, 78.4% vs no chemotherapy, 54.7%; p < 0.001). Even when controlling for all of the significant variables, the administration of chemotherapy remained a predictor of decreased mortality (HR = 0.57 (95% CI, 0.54–0.60); p < 0.001). LIMITATIONS: This study was limited by its retrospective, population-based design. CONCLUSIONS: Patients with T3N0 colon cancer with inadequate lymph node harvest who receive adjuvant chemotherapy have increased overall survival. Despite this survival benefit, a fraction of these patients receive adjuvant chemotherapy. Barriers to chemotherapy are multifactorial.